Studies on Sexual Violence in the Book of Tafsir and Hadith: Studi terhadap Kekerasan Seksual dalam Kitab Tafsir dan Hadis - Yahya, Nur Edi Prabha Susila (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The book of tafsir and hadith contains many lessons and wisdoms, one of them is to provide solutions to every human problem, especially today's problems such as sexual violence. This article will try to criticize how and what sexual violence is seen from the book of tafsir and hadith. This article is a qualitative research, with a critical perspective. The primary data source used is the book of tafsir, namely ibnu katsir, by examining QS.Yusuf verse 23 and examining the hadiths that talk about sexual violence in the Book of Hadith. Secondary data sources are writings in journal articles, books and the web. This article applies the fragmentation of the story in QS.Yusus verse 23 to find forms of sexual violence in the book of tafsir and hadith. At the end of this research, it is found that there is a form of sexual abuse within the framework of sexual violence obtained from examining QS. yusuf verse 23 and hadith about the prohibition of sexual violence. The theoretical implication of this article is the redefinition of the form of sexual violence in the books of interpretation and hadith.